Social impact of sport loads as a motivator for the practice of sports activities in the educational environment of a higher education institution - Vitaliy N. Avsiyevich; Zhassyn S. Mukhambet; Ihor Yu. Robak; Oleksandr V. Chernukha; Natalya V. Zakharchenko (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. The present study shows that sport loads for student environment determine not only the possibility of successful educational or scientific activities, but also successful social activity. The paper’s authors consider sports’ social meaning in higher education institutions as a function of implementing applied activities with correlation with successful professional medium. The relevance of the paper is in that doing sports in education institution is perceived not only as a part of the pedagogical load of topics from the general professional cycle, but also as a means of students’ socialization. The subject under study is students’ predisposition to implement the postulates of independent exercising. As a novelty, the issues of the development of motivation for students to do sports were studied. The main thesis of the research is to form a general idea on possibilities and motivation, as well as to carry out a complex evaluation of students’ readiness to do sports independently, without professors’ participation. A promising input is the testing of organizational-pedagogic conditions, and the integration of physical education and independent sports.